Fixed Points of Meromorphic Solutions for Some Difference Equations. (21st May 2013) - Chen, Zong-Xuan; Shon, Kwang Ho
Abstract : We investigate fixed points of meromorphic solutionsy ( z ) for the Pielou logistic equation and obtain some estimates of exponents of convergence of fixed points ofy ( z ) and its shiftsy ( z + n ), differencesΔ y ( z ) = y ( z + 1 ) − y ( z ), and divided differencesΔ y ( z ) / y ( z ) .